New data on the microvertebrate fauna from the Jurassic - Cretaceous transition site of Ksar Metlili (Anoual Sycline, eastern Morocco): significance for African and Gondwanan vertebrate evolution - (:unkn) unknown (My University, 2018)
The Jurassic-Cretaceous transition is a critical period for continental vertebrate evolution. Some major modern terrestrial vertebrate groups (e.g., lissamphibians, squamates, mammals and birds) and angiosperms emerged at this time, in the key palaeogeographic context of Pangea fragmentation and early evolution of Gondwanan and Laurasian faunas, which is accompanied by an abrupt cooling and a global drop in sea level.This work aims at improving our very poor knowledge of Gondwanan and especially African faunal palaeobiodiversity and evolution at this time, with the study of the two successive Moroccan microvertebrate faunas of Ksar Metlili (Berriasian, Early Cretaceous?) and Guelb el Ahmar (Bathonian, Middle Jurassic) from the Anoual Syncline. These faunas are among the richest known for the Mesozoic of the whole Gondwana. Morocco is a key region for this issue because of its geographical position on the African shores of the Tethys, well placed to record faunal interchanges between Laurasia and Gondwana. Furthermore, the diverse faunal associations preserved in the Anoual microvertebrate sites provide a better picture of African and Gondwanan palaeoecosystems, including some uncommon species rarely found in macroremain sites.Here we focus on the Ksar Metlili site, which produced more than 24,500 microvertebrate remains representing 28 species of 8 main groups, from selachians to mammals, that were identified and studied using comparative anatomy, taxonomic and statistical approaches. It includes remarkable taxa: the oldest therian mammals from Gondwana (and one of the richest Mesozoic mammal assemblages), some of the last known non-mammalian cynodonts, a basal ornithopod, a possibly freshwater teleosaurid crocodylomorph, and some of the scarce choristoderan reptiles and albanerpetontid amphibians known from Gondwana. A large scale faunal comparative study of Ksar Metlili with some closely aged sites, such as Guimarota (Kimmeridgian, Late Jurassic, Por
Keywords: African Research